2015
DOI: 10.1038/modpathol.2014.155
|View full text |Cite
|
Sign up to set email alerts
|

NY-ESO-1 (CTAG1B) expression in mesenchymal tumors

Abstract: New York esophageal squamous cell carcinoma 1 (NY-ESO-1, CTAG1B) is a cancer-testis antigen and currently a focus of several targeted immunotherapeutic strategies. We performed a large-scale immunohistochemical expression study of NY-ESO-1 using tissue microarrays of mesenchymal tumors from three institutions in an international collaboration. A total of 1132 intermediate and malignant and 175 benign mesenchymal lesions were enrolled in this study. Immunohistochemical staining was performed on tissue microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 31 publications
3
47
0
Order By: Relevance
“…36,37 NY-ESO-1 expression was observed not only on dedifferentiated but also on conventional chondrosarcoma. 38 Importantly, the matched primary tumor and subcutaneous metastasis evaluated in one patient displayed discordant PD-L1 expression. Also, the higher proportion of FoxP3 + T regulatory cells in metastases compared with primary tumors may suggest a specific role of these immunosuppressive cells in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 NY-ESO-1 expression was observed not only on dedifferentiated but also on conventional chondrosarcoma. 38 Importantly, the matched primary tumor and subcutaneous metastasis evaluated in one patient displayed discordant PD-L1 expression. Also, the higher proportion of FoxP3 + T regulatory cells in metastases compared with primary tumors may suggest a specific role of these immunosuppressive cells in later stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…CTAG1B) has recently shown to be almost universally expressed in MLS (89–100%). 2830 NY-ESO-1 expression is normally limited to germ cells making it a good cancer immunotherapeutic target. 31;32 …”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic T lymphocytes (CTL) are critical effectors of tumor cell killing in animal models, and intense CTL infiltration correlates with good prognosis in sarcomas (43,44). To stimulate CTL responses, MHCI-directed peptide vaccines have been pursued extensively, (45,46). Trials of such vaccines have historically shown disappointing clinical effects (47), likely due in part to insufficiency of vaccine adjuvants but also to the mutability of advanced cancers and to mechanisms of immunoevasion.…”
Section: Advances In Immunotherapymentioning
confidence: 99%